2020
DOI: 10.1371/journal.pone.0231665
|View full text |Cite
|
Sign up to set email alerts
|

CCNB2 and AURKA overexpression may cause atypical mitosis in Japanese cortisol-producing adrenocortical carcinoma with TP53 somatic variant

Abstract: Background Many genomic analyses of cortisol-producing adrenocortical carcinoma (ACC) have been reported, but very few have come from East Asia. The first objective of this study is to verify the genetic difference with the previous reports by analyzing targeted deep sequencing of 7 Japanese ACC cases using next-generation sequencing (NGS). The second objective is to compare the somatic variant findings identified by NGS analysis with clinical and pathological findings, aiming to acquire new knowledge about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Borges et al observed more aggressive disease in tumors with overexpression of AURKA and AURKB and presumed that the inhibition of these proteins could be a promising approach for the treatment for ACC [ 26 ] by using Aurora-specific degraders [ 138 ]. However, only in vitro data exist thus far [ 139 , 140 ]. Lira et al [ 123 ] discussed IGF1R inhibition as a possible target, but the in vitro data were not convincing [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Borges et al observed more aggressive disease in tumors with overexpression of AURKA and AURKB and presumed that the inhibition of these proteins could be a promising approach for the treatment for ACC [ 26 ] by using Aurora-specific degraders [ 138 ]. However, only in vitro data exist thus far [ 139 , 140 ]. Lira et al [ 123 ] discussed IGF1R inhibition as a possible target, but the in vitro data were not convincing [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, the overexpression of CCNB2 in tumor tissues has been shown to be an unfavorable prognostic biomarker in many human cancers, including gastric cancer, 22 breast cancer, 23 pituitary adenoma, 24 nasopharyngeal carcinoma, 25 and adrenocortical carcinoma. 26 The results of bioinformatics analysis showed that mRNA expression of CCNB2 was significantly associated with TNBC patients’ prognosis. Owing to the small sample size of TNBC, this study has certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary clinical studies have been conducted to validate the efficacy and safety of Aurora kinase inhibitors in AML [ 48 50 ]. Although the association of TP53 mutation and AURKA expression has been rarely studied previously for AML, it was explored in solid tumors with high frequency of TP53 variants, including adrenocortical carcinoma [ 51 ], pancreatic cancer [ 52 ], head and neck cancer [ 53 ], hepatocellular carcinoma [ 54 ] and ovarian cancer [ 55 ]. Moreover, in cancer cell lines lacking p53, resulting from genetic engineering to express HPV16-E6 oncoprotein or siRNA targeting TP53, the inhibitor of Aurora kinases (VX680) induced apoptosis was enhanced in comparison with cell lines with wide-type p53 [ 56 ].…”
Section: Discussionmentioning
confidence: 99%